Early developments in gene-expression profiling of breast tumors: potential for increasing black–white patient disparities in breast cancer outcomes?. (November 2011) - Odierna, Donna H; Afable-Munsuz, Aimee; Ikediobi, Ogechi; Beattie, Mary; Knight, Sara; Ko, Michelle; Wilson, Adrienne; Ponce, Ninez A
New prognostic tests, such as gene-expression profiling (GEP) of breast tumors, are expected to prolong survival and improve the quality of life for many breast cancer patients. In this article, we argue that GEP has not been adequately validated in minority populations, and that both biological and social factors might affect the broad utility of these tests in diverse populations. We suggest that the widespread use of this technology could potentially lead to suboptimal treatment for black women, resulting in a further increase in black–white patient disparities in treatment response, morbidity and mortality rates. We argue for the need to build a large and diverse evidence base for GEP and other emerging technologies in personalized medicine.